(untitled) (Applied Biological Research, 2023)
An in vitro study was conducted to assess the effect of using rice gluten meal as a substitute of soybean meal (SBM) in ruminant diet. The SBM comprising 12.5% whole diet [total mixed ration (TMR)] was substituted by rice gluten meal (RGM) on w/w basis at 0, 25, 50, 75 and 100% level. In vitro dry matter disappearance (IVDMD), organic matter disappearanc(IVOMD), net gas production, methane production and fermentation efficienof TMRs was assessed. The chemical composition of TMRs revealed decrease in total ash, acid detergent fiber and total carbohydrate contents and increase in organic matter, crude protein, ether extract, neutral detergent fiber, acid detergent lignin, hemicellulose, neutral detergent insoluble crude protein and acid detergent insoluble crude protein contents with increase in RGM in TMRs. No significant difference in net gas production, IVDMD and IVOMD was observed between the TMR treatments having graded levels of RGM and control. The NH3-N in TMRs declined with increase in RGM and was highest (P<0.05) in control. The relative proportion of propionic acid and isovaleric acid was highest in TMR 3 (50% RGM replacing SBM); whereas relative proportion of butyric acid was lowest in TMR 3. CH4 production showed decline with increase in RGM in TMRs beyond 25% level replacing SBM. The H-recovery was lowest in control TMR. The hydrogen consumed via CH4 as compared to the hydrogen consumed via VFA was lowest in TMR 3. The fermentation efficiency was highest in TMR 3. Thus, RGM could replace up to 100% of soybean meal in TMR of ruminants without any adverse effect on nutrient digestibility which is equivalent to 12.5% of whole dietary dry matter.